The effects of a change in the point system on immigration - Chemin, Matthieu (2016)
In 2001, Quebec changed its point system, a system that selects immigrants based on specific observable characteristics. The explicit objective was to increase the number of French-speaking immigrants, with no deterioration in overall labor market performance. To achieve this, points for French and education (specifically bachelor’s degrees) were increased. In parallel, points for a subjective assessment of “adaptability” were decreased. In line with the initial objective, we find more French-speaking immigrants with bachelor’s degrees, and no worsening in labor market outcomes after the reform. These results hold in a difference-in-differences and triple differences analysis. This paper shows how point systems can be used to shape the immigrant workforce according to policy goals.